2004
DOI: 10.1529/biophysj.103.035790
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Charge-Induced Molecular Alignment of Biomolecules Dissolved in Dilute Liquid-Crystalline Phases

Abstract: Alignment of macromolecules in nearly neutral aqueous lyotropic liquid-crystalline media such as bicelles, commonly used in macromolecular NMR studies, can be predicted accurately by a steric obstruction model (Zweckstetter and Bax, 2000). A simple extension of this model is described that results in improved predictions for both the alignment orientation and magnitude of protein and DNA solutes in charged nematic media, such as the widely used medium of filamentous phage Pf1. The extended model approximates t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 71 publications
(85 reference statements)
5
126
0
4
Order By: Relevance
“…XlePABP2-TRP bound the A 16 and A 30 RNAs (Fig. 1D) (16) yielded an excellent correlation coefficient (R ϭ 0.99) with one of the three principal axes of the alignment tensor coincident with the 2-fold symmetry axis of the homodimer. In support of the NMR analysis, gel filtration chromatography indicated that the XlePABP2-TRP protein eluted as a single peak with a retention volume that indicated a molecular mass of 28 kDa, approximately twice its predicted size of 16 kDa (Fig.…”
Section: Xlepabp2-trpmentioning
confidence: 89%
See 1 more Smart Citation
“…XlePABP2-TRP bound the A 16 and A 30 RNAs (Fig. 1D) (16) yielded an excellent correlation coefficient (R ϭ 0.99) with one of the three principal axes of the alignment tensor coincident with the 2-fold symmetry axis of the homodimer. In support of the NMR analysis, gel filtration chromatography indicated that the XlePABP2-TRP protein eluted as a single peak with a retention volume that indicated a molecular mass of 28 kDa, approximately twice its predicted size of 16 kDa (Fig.…”
Section: Xlepabp2-trpmentioning
confidence: 89%
“…A recombinant version of the protease-resistant domain (XlePABP2-TRP) was compared with the intact XlePABP2 protein in binding assays by using poly(A) RNAs (13). XlePABP2-TRP bound the A 16 and A 30 RNAs (Fig. 1D) (16) yielded an excellent correlation coefficient (R ϭ 0.99) with one of the three principal axes of the alignment tensor coincident with the 2-fold symmetry axis of the homodimer.…”
Section: Xlepabp2-trpmentioning
confidence: 99%
“…However, the measurement of RDCs corresponding to an additional two independent alignments now provides a more refined view, indicating that a specific tertiary structural arrangement, not inconsistent with a nativelike topology, also persists in the denatured state. Since the mechanisms of electrostatic alignment require an asymmetric distribution of ionizable groups, either on the surface where they mediate transient binding or globally as described by a multipole expansion, 13 these data demonstrate an asymmetry in the distribution of charged residues, in addition to an asymmetry in the distribution of bond vectors. From the observed ensembleaveraged distribution of backbone orientations, one can view a denatured protein as spanning three-dimensional space with a large heterogeneous distribution of conformations yet unable to access all possible segment orientations.…”
mentioning
confidence: 87%
“…Alignment was assessed by measuring the D 2 O splitting (19 Hz). The program PALES (20) was used for the calculation of the magnitude and orientation of the sterically induced alignment tensor (see below for details). NMR data were processed using Topspin (Bruker, Karlsruhe) and analyzed with SPARKY 3 (37).…”
Section: Subcloning Expression and Purification Of Myt1 Constructs-mentioning
confidence: 99%